Gamma Knife Radiosurgery of Distal Aneurysm: A Case Series - Liscak, Roman; Vymazal, Josef; Chytka, Tomas (Stereotactic and functional neurosurgery, 2021)
A series of 3 patients (35-60 years old) with bleeding distal aneurysm not associated with AVM who underwent radiosurgery by gamma knife are reported. One isocentre centralized over the aneurysm was used; peripheral dose 24-28.8 Gy was applied. Control angiography 20-36 months after gamma knife surgery (GKS) demonstrated obliteration of both the aneurysm and the feeding artery, without deterioration of the neurological symptoms. Our case series implies that GKS might serve as a safe mini-invasive technique in the treatment of selected distal aneurysms.
Keywords: dospělí; Aneurysm; aneurysma; lidé středního věku; radiochirurgie; lidé; Radiosurgery; Arteries; Middle Aged; arterie; Adult; Humans